British created Hinduism and Brahmins created the myth that India is Bharat: G Aloysius - Aloysius, G (Prabuddha: Journal of Social Equality; Vol 2 No 1 (2018): Myths underlying brahmin supremacy and white supremacy, 2018)
What I have done here is to historically trace how the earlier and very localized brahmanical svabhava through the operations of colonialism, orientalism, and nationalism, has become the nationalized, naturalized and accepted brahminical svabhava with control over everything. It is a historical development. At a national level, colonialism helped brahmanism. But this was also taken advantage of by a few people saying it is the British who developed caste. That is why I stick to the geographical entity: Brahmin influence was exerted in certain areas only, that means it existed prior to the coming of the British, but not everywhere. British took up the localized dominance (as general dominance) and this became the modern Indian nationalistic and universal. And today it is experienced as the brahmanical svabhava. Many of the middle-class values are brahmanical values for us, not necessarily limited to brahmins. Everyone, including Dalit Bahujan are influenced by it, middle-class life is a brahmanically expressed life.